Is laparoscopic totally extra peritoneal repair of hernia (TEP) superior than trans-abdominal preperitoneal (TAAP) mesh repair of inguinal hernia- our experience from a tertiary care hospital, Kolkata - Gangopadhyay, Ambar; Ghosh, Bikash Chandra (Asian Journal of Medical Sciences, 2018)
Background: The most common laparoscopic techniques for inguinal hernia repair are transabdominal preperitoneal (TAPP) repair and totally extraperitoneal (TEP) repair. In TAPP a mesh is placed through peritoneal incision over possible sites of hernia by going into peritoneal cavity, where as in TEP the peritoneal cavity is not entered and a mesh is used to seal the hernia from outside the peritoneum. Aims and Objectives: The aim of the current study was to compare the outcome of Total Extra- peritoneal (TEP) versus Trans-abdominal Pre-peritoneal (TAPP) repair of inguinal hernia, where both can be done. Materials and Methods: The current randomized control study was conducted among eighty patients of inguinal hernia. Of these, the sampling was done through random allocation of patients for TEP (Group-I) and TAPP (Group-II), comprising forty patients in each group. All patients irrespective of group were observed for pain (by VAS Score), mean operative time, duration of hospital stay, days taken to resume their normal activities, intra-operative and early post-operative complications and recurrence if any. Results: The pain in both groups was insignificant until one day but highly significant differences (p<0.0001) were observed by end of day 2 and 1 month, showing higher degree of pain in TAPP with respect to TEP procedure. The differences in mean operative time for surgery was highly significant (p<0.0001) with mean time of 86.72 min (TAPP) and 99.72 (TEP). The duration of hospital stay was higher in TAPP (5.2 days) compared to TEP (2.6 days). The mean time to return to normal activities was 10.8 days (TAPP) and 6.2 days (TEP) which was highly significant (p<0.0001). The recurrence though occurred only in one patient in TEP group which was negligible. The other post-operative complications was seroma (8 cases; TAPP) versus (1 case; TEP) and it was highly significant (p<0.0001). The port site infection was in 20 % patients (8/40) in TAPP compared to 2.5% (1/40) in TEP group. Conclusion: The TEP is comparatively superior than TAPP procedure in terms of post-operative complications, duration of hospital stay and return to normal activities. Asian Journal of Medical Sciences Vol.9(6) 2018 20-24